2012
DOI: 10.1182/blood-2011-07-365346
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting dynamic responses in vivo of the Bcl-xL and Bim erythropoietic survival pathways

Abstract: Survival signaling by the erythropoietin (Epo) receptor (EpoR) is essential for erythropoiesis and for its acceleration in hypoxic stress. Several apparently redundant EpoR survival pathways were identified in vitro, raising the possibility of their functional specialization in vivo. Here we used mouse models of acute and chronic stress, including a hypoxic environment and ␤-thalassemia, to identify two markedly different response dynamics for two erythroblast survival pathways in vivo. Induction of the antiap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 55 publications
2
33
0
Order By: Relevance
“…Bim is a crucial downstream determinant in regulating cell viability and survival, and previous studies have demonstrated that Bim is a potent pro-apoptotic protein in initiating the intrinsic apoptotic pathway under both physiological and pathological conditions [76,77]. Bim level was also regulated by erythropoietin (EPO)-mediated signaling in order to sustain the survival of erythroid cells [78,79]. Nevertheless, there is still no report on the implication of Bim alterations in regulating erythroid cells survival through miRNAs dependent manner to date.…”
Section: Discussionmentioning
confidence: 99%
“…Bim is a crucial downstream determinant in regulating cell viability and survival, and previous studies have demonstrated that Bim is a potent pro-apoptotic protein in initiating the intrinsic apoptotic pathway under both physiological and pathological conditions [76,77]. Bim level was also regulated by erythropoietin (EPO)-mediated signaling in order to sustain the survival of erythroid cells [78,79]. Nevertheless, there is still no report on the implication of Bim alterations in regulating erythroid cells survival through miRNAs dependent manner to date.…”
Section: Discussionmentioning
confidence: 99%
“…67 Koulnis et al have described EPO's slow yet persistent down-modulation of proapoptotic Bcl2-like 11 (Bim) in murine splenic EPCs. 68 Prior studies in HCD57 cells and primary murine EPCs also demonstrated EPOinduced Bim phosphorylation and proteasomal degradation. 69 The inhibition of Bim therefore represents one EPO-induced EPC survival mechanism.…”
Section: Epo/epor Cytoprotective Circuitsmentioning
confidence: 95%
“…69 The inhibition of Bim therefore represents one EPO-induced EPC survival mechanism. Post-EPO dosing, Bcl-xL levels in splenic EPCs transiently increase, 68 and in 32D-EPOR cells Bcl-xL is an EPO/ EPOR/STAT5 target gene. 70 These latter EPO effects, however, are not observed in erythroid colony-forming unit-like murine BM EPCs, 71 and EPO can efficiently cytoprotect Bclx-KO EPCs.…”
Section: Epo/epor Cytoprotective Circuitsmentioning
confidence: 99%
“…Differentiation of human erythroid progenitors was assessed by costaining cells with fluorochrome-conjugated antibodies to CD34 (a marker of immaturity), CD36 (an early marker of erythroid lineage commitment) (37), and glycophorin A (GPA) (a later marker of erythroid differentiation). Intracellular staining for erythroid PU.1 expression followed the guidelines of Koulnis et al (56). Specifically, human progenitors stained for CD34, CD36, and GPA underwent fixation and permeabilization using the BD Cytofix/Cytoperm Perm/Wash kit (BD Biosciences), followed by staining in the Perm/Wash solution with Alexa Fluor 488 rabbit anti-PU.1 antibody or matched control antibody (Cell Signaling Technology).…”
Section: Methodsmentioning
confidence: 99%